Ruang Publik dan Ekspresi Keberagaman Perempuan Berjilbab di Yogyakarta - Yuyun Sunesti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
Veiling in contemporary Indonesia does not have a single meaning. It has various meanings sincemany women have worn it with a variety of forms. This study uses a feminist ethnography, whereresearchers directly involved in the daily lives of respondents to know the meaning behind theirveils, the perception and the consequences of their veiling choices which is specifically recordedthrough the linkage between women